ANALISIS PROFITABILITAS SEBELUM DAN SESUDAH STOCK SPLIT PADA PERUSAHAAN YANG TERDAFTAR DI PT BURSA EFEK INDONESIA - Madani, Muhammad Nur (EKONOMIA, 2018)
This study refers to the signaling theory which states that the company does a stock split to deliver profitable private information about the future prospects of the company. The stock split announcement is considered a signal given by management to the public that the company has a good performance in the future.This study aims to determine whether there is a significant difference between the profitability of the company before and after the stock split event. The ratios used to measure profitability in this research are Gross Profit Margin, Net Profit Margin, Return on Assets and Return on Equity.The population in this study is companies listed on the Indonesia Stock Exchange 2009-2015 with a total of 15 go public companies where stock split was performed in 2012. The way of data processing and analysis was using t-test different test specifically paired samples t-test for testing an average of two samples associated using the SPSS program version 16.The result of statistical test by using paired samples t-test can be seen that from 4 ratio Profitability studied from 15 companies performing stock split, turns out that Gross Profit Margin, Net Profit Margin and Return on Assets ratio do not show significant different before and after stock split. Only Return on Equity has a significant difference after the company does a stock split.